Characteristics and Evolutionary Analysis of Photosynthetic Gene Clusters on Extrachromosomal Replicons: from Streamlined Plasmids to Chromids - Yanting Liu (American Society for Microbiology, 2019)
ABSTRACT Aerobic anoxygenic photoheterotrophic bacteria (AAPB) represent a bacteriochlorophyll a-containing functional group. Substantial evidence indicates that highly conserved photosynthetic gene clusters (PGCs) of AAPB can be transferred between species, genera, and even phyla. Furthermore, analysis of recently discovered PGCs carried by extrachromosomal replicons (exPGCs) suggests that extrachromosomal replicons (ECRs) play an important role in the transfer of PGCs. In this study, 13 Roseobacter clade genomes from seven genera that harbored exPGCs were used to analyze the characteristics and evolution of PGCs. The identification of plasmid-like and chromid-like ECRs among PGC-containing ECRs revealed two different functions: the spread of PGCs among strains and the maintenance of PGCs within genomes. Phylogenetic analyses indicated two independent origins of exPGCs, corresponding to PufC-containing and PufX-containing puf operons. Furthermore, the two different types of operons were observed within different strains of the same Tateyamaria and Jannaschia genera. The PufC-containing and PufX-containing operons were also differentially carried by chromosomes and ECRs in the strains, respectively, which provided clear evidence for ECR-mediated PGC transfer. Multiple recombination events of exPGCs were also observed, wherein the majority of exPGCs were inserted by replication modules at the same genomic positions. However, the exPGCs of the Jannaschia strains comprised superoperons without evidence of insertion and therefore likely represent an initial evolutionary stage where the PGC was translocated from chromosomes to ECRs without further combinations. Finally, a scenario of PGC gain and loss is proposed that specifically focuses on ECR-mediated exPGC transfer to explain the evolution and patchy distribution of AAPB within the Roseobacter clade. IMPORTANCE The evolution of photosynthesis was a significant event during the diversification of biological life. Aerobic anoxygenic photoheterotrophic bacteria (AAPB) share physiological characteristics with chemoheterotrophs and represent an important group associated with bacteriochlorophyll-dependent phototrophy in the environment. Here, characterization and evolutionary analyses were conducted for 13 bacterial strains that contained photosynthetic gene clusters (PGCs) carried by extrachromosomal replicons (ECRs) to shed light on the evolution of chlorophototrophy in bacteria. This report advances our understanding of the importance of ECRs in the transfer of PGCs within marine photoheterotrophic bacteria.